2015
DOI: 10.1007/s11920-015-0606-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology of Bipolar Disorder: Therapeutic Implication

Abstract: Multiple lines of evidence suggest that psychopathological symptoms of bipolar disorder arise in part from a malfunction of the circadian system, linking the disease with an abnormal internal timing. Alterations in circadian rhythms and sleep are core elements in the disorders, characterizing both mania and depression and having recently been shown during euthymia. Several human genetic studies have implicated specific genes that make up the genesis of circadian rhythms in the manifestation of mood disorders w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 134 publications
3
28
0
6
Order By: Relevance
“…Clinical trials of IPSRT indicate that increasing regularization is associated with a preventative impact on mood episode recurrence in patients with bipolar I disorder (Frank et al, 2005). There are also medications and other chronotherapies shown to be highly effective in regulating circadian rhythms (Dallaspezia and Benedetti, 2015), possibly resulting in less variable sleep durations. It is possible that a moving average of variability obtained through unobtrusive self-monitoring devices could inform or enhance such therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of IPSRT indicate that increasing regularization is associated with a preventative impact on mood episode recurrence in patients with bipolar I disorder (Frank et al, 2005). There are also medications and other chronotherapies shown to be highly effective in regulating circadian rhythms (Dallaspezia and Benedetti, 2015), possibly resulting in less variable sleep durations. It is possible that a moving average of variability obtained through unobtrusive self-monitoring devices could inform or enhance such therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that biological rhythm disturbances play an etiological role in bipolar disorder (BD) and that their regulation may contribute to a therapeutic effect [1,2]. Such disturbances can be detected not only during acute episodes of the illness but also in remission periods.…”
Section: Introductionmentioning
confidence: 99%
“…1 Impairments in sleep-wake patterns have been reported in patients with BD, who are also more likely to have the evening chronotype than control subjects. 2,3 Brazilian investigators introduced the Biological Rhythms Interview of Assessment in Neuropsychiatry (BRIAN) as a novel tool that allows complex assessment of biological rhythms 4 and showed that disruption in biological rhythms was greater in patients with BD than in those with major depression, and greater in both mood disorders than in community controls.…”
Section: Introductionmentioning
confidence: 99%